Implementing a reading program in secondary schools. - ASCD (Alexandria, Va : Association for Supervision and Curriculum Development, 2002)
Library has
Facilitator's guide.
Keywords: Curriculum planning (Reading) -- United States; Reading -- Study and teaching (Secondary) -- United States